2019
DOI: 10.1021/acsami.9b02381
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learning-Assisted Development and Theoretical Consideration for the Al2Fe3Si3 Thermoelectric Material

Abstract: Chemical composition alteration is a general strategy to optimize the thermoelectric properties of a thermoelectric material to achieve high-efficiency conversion of waste heat into electricity. Recent studies show that the Al 2 Fe 3 Si 3 intermetallic compound with a relatively high power factor of ∼700 μW m −1 K −2 at 400 K is promising for applications in low-cost and nontoxic thermoelectric devices. To accelerate the exploration of the thermoelectric properties of this material in a mid-temperature range a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 72 publications
2
77
0
Order By: Relevance
“…Active learning workflow A classic active learning strategy, Bayesian optimization, has been used many times to find materials with breakthrough properties. These works prove the effectiveness of active learning 20,21 . However, models in Bayesian optimization are limited to the probabilistic regression ones, excluding many other ML methods that also have outstanding performance, such as Support Vector Regression (SVR) 22 .…”
Section: Data Sourcesupporting
confidence: 58%
“…Active learning workflow A classic active learning strategy, Bayesian optimization, has been used many times to find materials with breakthrough properties. These works prove the effectiveness of active learning 20,21 . However, models in Bayesian optimization are limited to the probabilistic regression ones, excluding many other ML methods that also have outstanding performance, such as Support Vector Regression (SVR) 22 .…”
Section: Data Sourcesupporting
confidence: 58%
“…Recent evidence shows that the PF can be improved by controlling the conduction type of Al 2 Fe 3 Si 3 , which is further dictated by the ratio of Al/Si. Hou et al have employed a GPR model to predict PF for unknown compositions from existing experimental data. The input features were composition x in Al 23.5+ x Fe 36.5 Si 40− x and temperature.…”
Section: Applicationmentioning
confidence: 99%
“…Oliynyk et al (2016) found that electron count of B and difference in the atomic sizes of A and B are the most influential parameters in AB 2 C type of compounds using random forest ML algorithm. Hou et al (2019) used ML-based methods to optimize the Al/Si ratio in off-stochiometric Al 23.5+x Fe 36.5 Si 40Àx compounds for achieving highest power factor. Miller et al (2017) used high-throughput computations to screen 735 oxide materials for their thermoelectric properties and identified SnO as a potential n-type TE material.…”
Section: Introductionmentioning
confidence: 99%